Antiviral and immunomodulatory effect of zapnometinib in animal models and hospitalized COVID-19 patients - Füll, Yvonne; Schüssele, Lara M.; Hamza, Hazem; Hoffmann, Helen; Bauer, Martin; Stenglein, Stephan; Pötz, Oliver; Steinhilber, Andreas; Anselm, Viktoria; Delany, Mark W.; Van den Brand, Judith M. A.; Van Amerongen, Geert; et al. (Frontiers in Immunology, 2025)
IntroductionIn severe COVID-19, direct-acting antiviral drugs were not effective in hyperinflammatory stages and steroid treatment may weaken host immunity. The MEK inhibitor zapnometinib, as a host-targeting drug, has demonstrated promising efficacy against severe acute viral infections. Proof-of-concept for the innovative approach was presented in a clinical Phase 2 trial with hospitalized COVID-19 patients.MethodsThe antiviral and immunomodulatory potential of zapnometinib was investigated in samples obtained from COVID-19 patients enrolled in a Phase 2 clinical trial (RESPIRE), as well as in a SARS-CoV-2 Syrian hamster model, an acute lung injury mouse model, and in cell culture. The antiviral activity of zapnometinib was assessed using viral load reduction assays and RT-qPCR. Cytokines and chemokines were analyzed via ELISA and RT-qPCR. Alterations in T and B cells from COVID-19 patients were analyzed using flow cytometry. Biomarker analysis in hamster serum was conducted to monitor potential toxic effects.ResultsZapnometinib reduced SARS-CoV-2 viral load in hospitalized COVID-19 patients, in the hamster model and in various highly pathogenic coronaviruses in vitro. Pro-inflammatory cytokines and chemokines decreased in COVID-19 patients, in a lung injury mouse model, and in vitro in primary human blood cells treated with zapnometinib. In the hamster model, zapnometinib alleviated SARS-CoV-2-mediated lung pathology. In patients with COVID-19, zapnometinib increased T and plasma B cells.ConclusionUnlike direct-acting antivirals, zapnometinib’s dual effect highlights its therapeutic potential in the treatment of severe acute viral infections, with favorable antiviral and immunomodulatory properties.